PENERAPAN MODEL DISCOVERY LEARNING BERBANTUAN MEDIA DIGITAL INTERAKTIF EDUCAPLAY UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN LITERASI SAINS SISWA SEKOLAH DASAR - Ika Kusumawati; Ardi Prabowo; Nuni Widiarti; Decky Avrilianda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to address the low level of students’ conceptual understanding and science literacy in learning the Solar System at SDN 1 Brumbung. The research aimed to examine the implementation of the Discovery Learning model assisted by interactive digital media Educaplay and to analyze its effect on improving students’ conceptual understanding and science literacy. This study employed a mixed-method approach with a sequential explanatory design. The participants were 19 sixth-grade students. Quantitative data were collected through pretest and posttest instruments measuring conceptual understanding and science literacy, while qualitative data were obtained through classroom observations and field notes. Quantitative data were analyzed using regression analysis, and qualitative data were analyzed using thematic analysis. The results showed that the implementation of Discovery Learning assisted by Educaplay was carried out effectively and significantly improved students’ conceptual understanding and science literacy. In addition, students demonstrated higher engagement and active participation during the learning process. These findings indicate that integrating Discovery Learning with interactive digital media can provide meaningful learning experiences and enhance students’ higher-order thinking skills in elementary science education.